Congenital Kyphoscoliosis in Monozygotic Twins: Ten-Year Follow-up Treated by Posterior Vertebral Column Resection (PVCR): A Case Report. Issue 17 (April 2016) - Chang, Dong-Gune; Yang, Jae Hyuk; Lee, Jung-Hee; Kim, Young-Hoon; Kim, Jin-Hyok; Suh, Seung-Woo; Ha, Kee-Yong; Suk, Se-Il
Abstract : Abstract: The etiology of congenital scoliosis and its development remains unclear and has not yet been fully identified, even there are theories that congenital scoliosis could be derived from the failure of formation or failure of segmentation, which are etiologically heterogeneous with genetic, epigenetic, and environmental factors contributing to their occurrence. We reported a case of long-term follow-up after posterior vertebral column resection (PVCR) in both identical twins with similar congenital kyphoscoliosis at thoracolumbar levels. Twin I had been noticed by his parents to have asymmetry of his back at age 5 years, but no treatment was given. Twin II was first noticed to have a spinal problem at 11 years of age by his parents. Overtime, spine of both twins became further deviated to the left with kyphosis and was referred to our hospital. Both monozygotic twins were treated by PVCR and satisfactory results were demonstrated at 10-year follow-up. This case is the first report on the surgical treatment with PVCR, almost simultaneously, in both identical twins who had similar congenital vertebral anomalies causing kyphoscoliosis. Both identical twins with congenital kyphoscoliosis had undergone surgical correction by PVCR, anterior support with a mesh cage and posterior fusion using pedicle screws at the age of 14 years and achieved a satisfactory correction and a stable spine without curve progression with 10-year follow-up.